Wiley Federal Government Auditing : Laws, Regulations, Standards, Practices, & Sarbanes-Oxley - Kearney, Edward F. ; Fernandez, Roldan ; Green, Jeffrey W. and Zavada, David M. (Hoboken John Wiley & Sons, 2013)
Now in a Second Edition, Federal Government Auditing is a single-source reference guide that assists professionals and nonprofessionals performing audits unique to federal departments and agencies, to contractors and grantees, universities, and other non-profits
Include Index
Keywords: United States -- Finance, Public--Auditing--Law and legislation -- Finance, Public--Auditing